Brief Report: Telehealth Music-Enhanced Reciprocal Imitation Training in Autism: A Single-Subject Feasibility Study of a Virtual Parent Coaching Intervention. - Liu, Talia; Martinez-Torres, Keysha; Mazzone, Julie; Camarata, Stephen; Lense, Miriam (Journal of Autism & Developmental Disorders, 2025)
Purpose: Telehealth delivery increases accessibility of parent-mediated interventions that teach parents skills and support autistic children's social communication. Reciprocal Imitation Training (RIT), an evidence-based Naturalistic Developmental Behavioral Intervention (NDBI) focused on imitation skills, a common difficulty in autism, holds promise for telehealth-based parent training. Imitation is also a core component of musical play during childhood and the affordances of musical play/song naturally shape parent–child interactions. We evaluate the feasibility of a music-based, telehealth adaptation of RIT—music-enhanced RIT (tele-meRIT)—as a novel format for coaching parents in NDBI strategies. Methods: This single-subject, multiple baseline design study included 4 autistic children (32–53 months old) and their mothers. Parent–child dyads were recorded during 10-min free play probes at baseline, weekly tele-meRIT sessions, and one-week and one-month follow-up. Probes were coded for parents' RIT implementation fidelity, parent vocal musicality, and children's rate of spontaneous imitation. Results: No parent demonstrated implementation fidelity during baseline. All parents increased their use of RIT strategies, met fidelity by the end of treatment, and maintained fidelity at follow-up. Parent vocal musicality also increased from baseline. Intervention did not consistently increase children's imitation skills. A post-intervention evaluation survey indicated high parent satisfaction with tele-meRIT and perceived benefits to their children's social and play skills more broadly. Conclusion: Implementing tele-meRIT is feasible. Although tele-meRIT additionally involved coaching in incorporating rhythmicity and song into play interactions, parents achieved fidelity in the RIT principles, suggesting one avenue by which music can be integrated within evidence-based parent-mediated NDBIs.